2019
DOI: 10.3390/ijms20071733
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Histamine in the Pathophysiology of Asthma and the Clinical Efficacy of Antihistamines in Asthma Therapy

Abstract: Mast cells play a critical role in the pathogenesis of allergic asthma. Histamine is a central mediator released from mast cells through allergic reactions. Histamine plays a role in airway obstruction via smooth muscle contraction, bronchial secretion, and airway mucosal edema. However, previous clinical trials of H1 receptor antagonists (H1RAs) as a treatment for asthma were not successful. In recent years, type 2 innate immunity has been demonstrated to be involved in allergic airway inflammation. Allergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 69 publications
1
87
0
4
Order By: Relevance
“…However, previous clinical trials with antihistamines in the asthma treatment were not successful. This happens because asthma is an extremely complex disease that involves more than just histamine as a pathogenic mediator . However, antihistamines may have a role in patients with allergic asthma and rhinitis.…”
Section: Indications In Childrenmentioning
confidence: 99%
“…However, previous clinical trials with antihistamines in the asthma treatment were not successful. This happens because asthma is an extremely complex disease that involves more than just histamine as a pathogenic mediator . However, antihistamines may have a role in patients with allergic asthma and rhinitis.…”
Section: Indications In Childrenmentioning
confidence: 99%
“…Cheryl et al (2017) reported that mindfulness meditation led to a moderate improvement in lung functions in a study population composed of patients with asthma. This can be explained by the fact that mindfulness meditation is a stressreduction intervention and stress leads to histamine release which can trigger broncho-constriction and mucus hypersecretion in asthmatics (Yamauchi and Ogasawara, 2019). Kabat-Zinn et al (2017) documented that mindfulness meditation during phototherapy can increase the rate at which the halfway and the end phases of psoriatic lesions clearing is attained by patients with moderate to severe psoriasis.…”
Section: General Positive Physiological Effects Of Mindfulness Meditamentioning
confidence: 99%
“…Nasal congestion has been reported during anaphylactic episodes, and has the potential to interfere with IN epinephrine in the treatment of anaphylaxis [20,21]. During an anaphylactic or allergic event, the release of inflammatory mediators, such as histamine, contribute to vasodilation [22,23]. Increased vasodilation can result in edema and swelling of the nasal mucosa, impeding air flow and increasing nasal secretions [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…During an anaphylactic or allergic event, the release of inflammatory mediators, such as histamine, contribute to vasodilation [22,23]. Increased vasodilation can result in edema and swelling of the nasal mucosa, impeding air flow and increasing nasal secretions [22,23]. However, alpha-adrenergic receptor agonists like epinephrine have known decongestant activity [24].…”
Section: Introductionmentioning
confidence: 99%